A review on the interval type-2 fuzzy systems. (12th May 2021) - Chandra, Prabhash; Agarwal, Devendra; Shukla, Praveen Kumar
Considering the benefits of the human decision making, the efforts have been executed to implement it in machines. The chronic problem addressed in this implementation is the representation and manipulation of human knowledge which is full of uncertainties and imprecision due to its subjective nature. To deal with this problem a strong mathematical framework is investigated known as fuzzy logic. Initially the concept of fuzzy set has been developed by extending the Boolean crisp set logic. Further, type-2 fuzzy systems and interval type-2 fuzzy systems are investigated. This paper reviews the approaches and systems developed under the category of interval type-2 fuzzy systems along with the interpretability and accuracy issues in fuzzy systems.